Evaluasi Penggunaan Antibiotik Pada Pasien Infeksi Saluran Pernapasan Atas Akut (Ispaa)Di Instalasi Rawat Inap RSUD Ungaran Kabupaten Semarang Tahun 2016 - GALIH SADEWA, SAHERTIAN, Dra. Nurul Mutmainah, M.Si., Apt (2017)
Acute Respiratory Infection (ARI) is an acute infection of the airway structure that interferes with the gas exchange process from the nose to the alveoli including its adnexa. ARI caused by viruses such as flu and influenza do not respond to antibiotics, whereas the ones caused by bacteria can be treated with antibiotics. Proper and rational use of antibiotics can have cost-effective effects, increased clinical effects, minimize drug toxicity and minimize the occurrence of resistance. The purpose of this study is to know the description of therapy and the accuracy of the use of antibiotics for patients diagnosed with Acute Upper Respiratory Infection (AURI) in Inpatient Installation of the District General Hospital Ungaran, Semarang Regency in 2016. This research was conducted by non-experimental method with retrospective data retrieval. The data obtained were analyzed descriptively to get an idea about the accuracy of antibiotics given to patients with Acute Upper Respiratory Infection (AURI). That was carried out by seeing Clinical Pathways of RSUD Ungaran in 2016, treatment standard from the Ministry of Health of the Republic of Indonesia in 2005 and WHO in 2003 to see the accuracy of indication, patient accuracy, drug accuracy and accuracy of dose. The results showed that from 100 samples in patients diagnosed with AURI at the District General Hospital of Ungaran in 2016, patients using ceftriaxone antibiotics were 57 cases, 11 cases of amoxicillin and cefotaxime of 9 cases while combination of two antibiotics were 20 cases and combination of three antibiotics were 4 cases. The indication accuracy rate was 100%, patient accuracy was 95%, 13% of drug accuracy and 8% of dose accuracy.